2022
DOI: 10.7759/cureus.21790
|View full text |Cite
|
Sign up to set email alerts
|

Sonography Findings Predict Testicular Viability in Pediatric Patients With Testicular Torsion

Abstract: Background: Testicular torsion poses a pediatric surgical emergency that necessitates rapid diagnosis and surgery to prevent testicular loss. We sought to determine whether any particular findings on Doppler ultrasound (US) were predictive of testicular viability in pediatric patients with testicular torsion.Materials and methods: We identified males between ages one and 18 years who experienced testicular torsion over a six-year period (January 1, 2015-December 31, 2020). All patients were evaluated at our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Typically, a twist of 450 degrees or more causes complete occlusion of blood flow to the testis 5 . Prolonged ischemia will cause marbling of the testis and correlates with poor prognosis 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a twist of 450 degrees or more causes complete occlusion of blood flow to the testis 5 . Prolonged ischemia will cause marbling of the testis and correlates with poor prognosis 10 .…”
Section: Discussionmentioning
confidence: 99%
“…USI is an efficient, practical, radiation-free and noninvasive method to diagnose TT. Despite the high diagnostic accuracy of USI for complete TT, it may lead to false-negative diagnoses in cases of incomplete TT [13] , [29] , [30] , [31] , [32] . As a novel imaging technique, PAI can exploit an sO 2 map of tissue to offer more valuable information [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Mushtaq et al reported a misdiagnosis rate of 12.5% in the case of TT, 17% for TAT, and 44% for epididymitis [22]. The literature remarks on the importance of US in enhancing the diagnostic power of clinical examination alone [23][24][25][26][27][28][29]. TAT's clinical management is not homogenous across the world.…”
Section: Discussionmentioning
confidence: 99%